Judicial Separation in Islamic Law (A Critical Analysis of Dissolution of Marriage Beyond Talaq in Pakistani Law) - Rabia Tus Saleha; Dr. Muhammad Amin Makki; Dr. Mudasra Sabreen (Al Manhal Research Journal, 2025)
This research explains the authority of šhara’i qāḍi for annulment and dissolution of marriage under Islamic Jurisprudence as elaborated by different schools of thought. Further, the rulings of four basic schools of thought are compared with Pakistani law. Dissolution of marriage by the qāḍī is different from talaq as the talaq occurs with the permission and consent of husband. While, the separation by qāḍī may occurs with the ruling of the judge that enables the woman to end the wedlock by forcing the husband. Generally, the last option of judicial separation is resorted in the cases where optional means of divorce or khul’ fails. Pakistani law has adopted these ways of separation to get rid of harmful relation between spouses. The primary purpose of judicial separation is to protect the woman from injustice as well as to discipline the man who does not respect the rights of his wife. Though, it is an ideal legal solution to address the problems of abuse against married women. Besides this, a condition of delegated divorce may be selected in the certificate of marriage in Pakistan to protect and overcome the abuse against women in family institution. However, this paper includes the matters of judicial separation exclusively. In Pakistan, two important statutes correspondingly, Dissolution of Muslim Marriages Act of 1939 and The Muslim Family Laws Ordinance of 1961, are enforced to deal with family matters. The validity of these two laws has always been controversial among religious circles and law makers. An important question that arises between the critics is associated with the legal separation (tafreeq šhara’i) between husband and wife without the pronunciation of talaq by the husband.